PERANCANGAN VIDEO DOKUMENTER TENTANG DAMPAK PANDEMI TERHADAP USAHA PRINT ADEVERTISING DI ROVELL ADVERTISING - Hafizh Arif Alfarsy Rukmana; Adrian Alexander Suripatty (DAS Institute, 2022)
Advertising is one way to promote a product or service. There are various ways to create advertisements, one of which is by making large banners or billboards, commonly called print advertising. In recent years, many entrepreneurs have become interested in starting a company in print advertising. Not because there is no reason, many entrepreneurs are starting to look at this business opportunity, because it turns out that many UMKM need to promote the products or services they offer, unfortunately in the last three years there has been an outbreak of the covid 19 pandemic that has affected the economy of the Indonesian state which has made Entrepreneurs work hard to maintain their business. This documentary video was made to provide information about the impact of the pandemic on the print advertising business.